The emerging role of blood-based biomarkers in early detection of colorectal cancer: A systematic review - Faris Shweikeh; Yuhao Zeng; Abdur Rahman Jabir; Erica Whittenberger; Saurav P. Kadatane; Yuting Huang; Mohamad Mouchli; Dani Ran Castillo (Cancer Treatment and Research Communications)
Background: Colorectal cancer (CRC), the third most commonly diagnosed and second most lethal cancer worldwide, necessitates efficient early detection strategies to improve patient outcomes. This review evaluates the promise of novel blood-based biomarkers for early detection of CRC. Methods: A systematic review, registered with PROSPERO (CRD42024513770) and adhering to PRISMA guidelines, was conducted across multiple databases from January 1st, 2020 to December 31st, 2022. The comprehensive search strategy centered on sensitivity, specificity, and AUC-ROC of multiple types of molecular blood biomarkers. Results: Of total of 142 included articles, 59 were on protein, 58 on RNA, and 21 on DNA. The investigation into DNA biomarkers revealed that cfDNA and ctDNA carry significant potential for early CRC diagnosis. For instance, methylation patterns in genes such as MYO1-G and NDRG4 exhibited high diagnostic accuracies with AUCs reaching up to 0.996. RNA biomarkers like miRNAs and circRNAs also showed promising results, with circ_0011536 achieving AUCs of 0.982. Protein biomarkers, contrasted with established cancer markers, unveiled notable candidates like Irisin and ANXA2, with AUCs surpassing 0.96. The review highlights several individual markers and panels with the potential to improve upon existing CRC screening tests. Conclusions: Despite the promise shown by the novel biomarkers, challenges persist, including small sample sizes, potential selection biases, and a lack of comprehensive cost-effectiveness analysis. Future research should focus on large-scale, multicenter, prospective studies across diverse populations. The findings advocate for an integrated biomarker approach, potentially revolutionizing CRC screening and aligning it with clinical realities through rigorous validation.